2017
DOI: 10.1001/jamapsychiatry.2016.2992
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sensory Processing With Higher-Order Cognition and Functioning in Schizophrenia

Abstract: Our brain is mapping the world…often that map is distorted, but it's a map with constant immediate sensory input.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Impaired auditory processing is a consistent finding in schizophrenia and is thought to lead to failures in one's ability to interact with the environment, contributing to delusional beliefs, hallucinations, social withdrawal, cognitive dysfunction, and decline in functioning (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These deficits have been extensively studied using event-related potentials (ERP) corresponding to early sensory processing events that occur within milliseconds following the reception of an auditory stimulus (7).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired auditory processing is a consistent finding in schizophrenia and is thought to lead to failures in one's ability to interact with the environment, contributing to delusional beliefs, hallucinations, social withdrawal, cognitive dysfunction, and decline in functioning (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These deficits have been extensively studied using event-related potentials (ERP) corresponding to early sensory processing events that occur within milliseconds following the reception of an auditory stimulus (7).…”
Section: Introductionmentioning
confidence: 99%
“…The association of sensory processing with higher-order cognition, including accurate identification of environmental sounds, supports the emerging strategy of targeting abnormalities in low-level auditory network dysfunction, which is increasingly viewed as a promising component of next-generation treatments (e.g., Fisher et al, 2009; Vinogradov & Nagarajan, 2017; Light & Swerdlow, 2014; Tarasenko et al, 2014, Thomas et al, 2017; Kantrowitz et al, 2016). The use of neurophysiologic biomarkers of early auditory processing (e.g., MMN, gamma oscillations) to predict and monitor response to these treatments (e.g., Perez et al, 2017; Swerdlow et al, 2016a, b; Light et al, in press) will accelerate the pace of translating findings from experimental medicine paradigms to clinical practice.…”
Section: Discussionmentioning
confidence: 87%
“…This involves transforming acoustic parameters, such as pitch, harmonicity, onset, timing, timbre, and spatial location into meaningful percepts based on previous experiences, all of which require accurate auditory perception. In patients with schizophrenia (SZ), auditory perception is profoundly impaired, contributing to bottom-up deficits associated with cognitive dysfunction, and, ultimately, social functioning (Thomas et al, 2017; Vinogradov & Nagarajan, 2017; Force et al, 2008; Kiang et al, 2009; Leitman et al, 2005, 2010; Javitt, 2009; Braff & Light, 2004; Rissling et al, 2014; Kirihara et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a body of work evaluating the effects of a cognitive training program that emphasizes auditory sensory processing has demonstrated significant treatment-related improvements in higher-level auditory and verbal functions in schizophrenia, such as verbal working memory and verbal learning [ 61 63 ]. Although this program includes training on both low-level auditory targets and higher-level functions such as verbal memory and learning, it was observed that training-related gains in speed of auditory processing, a specific perceptual target of this intervention, were associated with improvements in global cognition, suggesting that gains in lower-level perceptual processes may contribute to improvements in higher-order cognitive functions in schizophrenia [ 64 ]. In short, multiple lines of evidence converge to suggest that remediation of visual function is possible, and that it could lead to gains in higher cognitive and related functions.…”
Section: Significancementioning
confidence: 99%